Prevalence of uropathogens and antimicrobial susceptibility profile in outpatient from Jataí-GO - Moraes,Dayane (2014)
Introduction: Urinary tract infections (UTIs) affect people worldwide. Escherichia coli is the main agent of UTI, however the etiology may vary according to the age and sex of the patient. Regional variations in the prevalence and antimicrobial resistance should be considered for therapy choice. Objectives: This study aimed to conduct a survey on the main agents of UTI, and assess the resistance of these microorganisms, during the period of March 2010 to June 2012 in the city of Jataí-GO. Method: A retrospective cross-sectional study were performed, collecting data on the prevalence of uropathogens and their sensitivity profiles which were evaluated by disk diffusion method. Results: During this period, 2,181 urine cultures were evaluated, of which 510 (23.4%) were positive, predominantly female (81.4%) and aged between 21 and 64 years old (59.7%). The most frequently isolated microorganism was E. coli (61%), followed by Staphylococcus saprophyticus (9.4%), and Proteus (9.4%). The prevalence of these bacteria according to the patient sex has suffered a statistically significant change (p < 0.05). It was possible to detect high resistance rate of E. coli to some antibiotics of choice for UTI treatment, such as ampicillin (57.9 %), pipemidic acid (50.5 %), nalidixic acid (48.6 %), and trimethoprim-sulfamethoxazole (44.8%). Conclusion: These data demonstrate the need to know the reality of each region in order to establish an appropriate empirical therapy, when it is not possible to perform culture and antimicrobial susceptibility testing.